A Preliminary Study of the Relationship Between Built Environment of Open Space and Cognitive Health of Older People - Ruozhu YIN; Mei-yung LEUNG; Yueran LI (Journal of Contemporary Urban Affairs, 2023)
Many older people are facing various risks of cognitive impairment, while outdoor activities in open spaces may be helpful for their cognitive health. However, the effect of open spaces on cognitive health is unclear. This study aims to investigate the relationships between the cognitive health of older people and the built environment of open spaces. A questionnaire survey of 60 older people aged 60 and above was conducted. Results identified three major components of the built environment of open spaces, namely, planning, supporting facilities, and building services. According to the correlation and regression analysis, it is revealed that 8 BEOS items, including green ratio, a width of the pathway, maintenance of the whole garden, the color of green space, diversity of plants, location, and font of signage, artificial light of sitting area were positively related to memory, while only the size was negatively associated with memory. Only the green ratio could positively predict the concentration. The judgment was positively influenced by the green ratio, width of pathways, maintenance of the whole garden, color of green space and diversity of plants. A BEOS – cognitive health model for older people was built in this study. The results highlighted the importance of plants for cognitive health. Several recommendations, such as not-so-large sizes and diverse plants with vivid colors and signages with big fonts, etc., were proposed to improve the built environment of the open spaces and support the declining cognitive health of older people.